Sharia Financial And Banking Product Innovation In SMEs Development - Subkhan, Mohammad; Hardiyanto, Feri; Widya, Widya; Maghfiroh, Diana (International Journal of Social Research, 2023)
The financial product innovation that exists at the KHAS Kempek Micro Waqf Bank, Cirebon Regency is one of several sharia MFIs for community empowerment programs through the establishment of Sharia MFIs around Islamic boarding schools, which in its establishment was facilitated by the Financial Services Authority (OJK) and the Small Business Business Incubation Center (PINBUK). This study aims to find out how to optimize the use of Islamic products at Micro Waqf Banks for Islamic Financial and Banking Innovation in MSME Development. Method study using a qualitative approach to design descriptive analytical. Source of data used is primary data sources from data obtained by observing and interviewing directly from the source, namely at the KHAS Kempek Micro Waqf Bank, Cirebon Regency as well as collecting documentation from books, articles, journals, the internet and various other sources which are then processed and analyzed with stages of analysis which include data reduction, data display and verification as well as conclusions. Results from study shows that Islamic Financial and Banking Innovation Micro Waqf Bank KHAS Kempek Cirebon Regency for the Economic Empowerment of Micro Enterprise Actors (MSMEs) around Islamic Boarding Schools is operating with sharia principles that are committed to tackling the problem of poverty and inequality by providing access to capital to productive poor people or to micro-entrepreneurs around Islamic boarding schools to improve their standard of living and help them with loans that are unsecured or collateral and most importantly with very low margins, which are equivalent to 3% per year, by maximizing cash waqf funds in providing loans capital, coaching and evaluation. It was concluded that the KHAS Kempek Micro Waqf Bank, Cirebon Regency, had succeeded in empowering the micro-business actors around Islamic boarding schools with sharia principles.